Existence And Uniqueness Of Strong Solution For A Semi-Linear Wave Equation With Nonlinear Boundary Dissipation (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2019)
نهدف في هذا البحث إلى إثبات وجود ووحدانية حل قوي لمسألة القيم الحدية الابتدائية للمعادلة الموجية شبه الخطية مع شرط التبدد الحدي اللاخطي، بتحويلها إلى مسألة كوشي ذات معادلة تفاضلية مؤثرية من المرتبة الثانية في فضاء هلبرت، وذلك باستخدام صيغة غرين لثلاثية من فضاءات هلبرت. We aim in this research to study the existence and uniqueness of strong solution for initial-boundary values problem for a semi-linear wave equation with the nonlinear boundary dissipation, by transforming it to a Cauchy problem with second order operator differential equations in Hilbert space. Therefore, we transform it, using Green's formula for a triple of Hilbert spaces.